Improving the accuracy of thin metal film research using the eddy current method - Shmykov Danil; Malikov Vladimir; Katasonov Alexander; Voinash Sergey; Vornacheva Irina; Larin Oleg; Tansura Anton (EPJ Web of Conferences)
Based on the review of the current state and literature in the field of non-destructive examination of thin metal films, it has been established that the optimal method for studying thin-film structures in terms of the performance/quality ratio is the non-destructive eddy current method. The main principles of constructing eddy current transducers are considered, the design of the developed overhead transformer miniature eddy current transducer with a ferrite core for studying the electrical conductivity of thin metal films is described. The structural diagram is given and the algorithm of operation of the hardware and software complex is described, the characteristics of the main components of the hardware of the hardware and software complex are given. The algorithm of operation of the software that controls the operation of the hardware and software complex and is responsible for processing and visualizing the results in a form convenient for the operator is described. A method for analyzing the rate of change of the eddy current transducer signal has been developed, allowing measurements of the sizes of defects and inhomogeneities of a thin metal film. The proposed method was used to study a thin metal film and showed a significantly increased accuracy in determining the boundaries and sizes of defects as a result of analyzing the rate of change of the ECT signal. The increase in accuracy was up to 7% compared to the analysis of the direct change in the amplitude of the ECT signal.